The Role of Social Values of Islamic Education in Shaping the Religious Character of Adolescents - Rohman, Ahmad Taufiq Hidayatur; Arisanti, Kustiana; Mansur, Rosichin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to examine the role of social values ​​of Islamic education in shaping the religious character of adolescents. The research method used is qualitative, with a literature study approach and content analysis of various relevant literature. Data and data sources in this study come from journal articles, books, and related documents published between 2020 and 2024. Data collection techniques are carried out through systematic literature searches using academic databases and digital libraries. Data analysis techniques use content analysis, where data is analyzed in depth to identify main patterns and themes related to the social values ​​of Islamic education and the formation of adolescent religious characters. The findings of the study indicate that social values ​​such as justice, equality, and social concern applied in Islamic education have a significant contribution to strengthening religious identity and increasing positive social behaviour in adolescents. The conclusion of this study confirms that the integration of Islamic social values ​​in the curriculum and school activities is very effective in shaping the religious character of adolescents. The implications of this study show the importance of implementing social values ​​in education to produce a young generation that is ethical and has integrity. Recommendations for further research are to develop more innovative strategies to address challenges in implementing these values, as well as explore the impact of external environmental influences such as social media on Islamic social values ​​education.